INVESTIGATING EFL TEACHER TRAINERS’ PRACTICES AND VIEWS OF LANGUAGE TEACHING AND DEVELOPING LEARNERS’ COMMUNICATIVE COMPETENCE IN KAZAKHSTAN - Zikrina, Zarina (Nazarbayev University Graduate School of Education, 2022)
The development of communicative competence in the English language is an instructional goal of secondary education in Kazakhstan. This objective is supported by policymakers and the media, who are advocating its practical utility for competing in a globalized world. With the heightened expectations and demands on school graduates, English language teaching and learning is changing to improve students’ educational achievements. To support and enhance the quality of education and ongoing teacher training in Kazakhstan, the potential of professional development system is utilized. In spite of the considerable implementation efforts, research in Kazakhstan suggests that the development of communicative competence in English remains a challenge for learners. Additionally, current research findings indicate that there is a mismatch between teachers’ and students’ views about the challenges of developing effective English communication skills in secondary schools in Kazakhstan. However, few studies have paid attention to the recent professional development programs for in-service English as a foreign language (EFL) teachers from the perspectives of teacher trainers. As a result, the purpose of this study is to investigate the practices and views of teacher trainers on Communicative Language Teaching (CLT) and the development of communicative competence in learners. To achieve the aims of the study, qualitative research design was followed and multiple research instruments employed, namely, questionnaires, semi-structured interviews and a documents analysis. The findings revealed that communicative competence is internalized as a quantifiable skill measured through international assessment frameworks and testing systems. Further, CLT is viewed as a student-centered approach with the focus on both form and meaning. At the same time, EFL teacher trainers identified classroom-level and societal-institutional constraints, namely, the presence of mixed-ability students, inconsistency in the content of English textbooks, and absence of a sustainable professional development system as impediments for successful CLT implementation. On this basis, the pointed out societal-institutional and classroom-level constraints in English language classrooms should be taken into account when designing professional development programs.
Keywords: Type of access: Open Access; EFL teacher trainers; Communicative Language Teaching; in-service teacher training